Association of Dietary Patterns Derived Using Reduced‐Rank Regression With Subclinical Cardiovascular Damage According to Generation and Sex in the STANISLAS Cohort. Issue 7 (9th April 2020) - Wagner, Sandra; Lioret, Sandrine; Girerd, Nicolas; Duarte, Kevin; Lamiral, Zohra; Bozec, Erwan; Van den Berghe, Laurie; Hoge, Axelle; Donneau, Anne‐Françoise; Boivin, Jean‐Marc; Mercklé, Ludovic; Zannad, Faiez; et al.
Abstract : Background: The diet impact on cardiovascular diseases has been investigated widely, but the association between dietary patterns (DPs) and subclinical cardiovascular damage remains unclear. More informative DPs could be provided by considering metabolic syndrome components as intermediate markers. This study aimed to identify DPs according to generation and sex using reduced‐rank regression (RRR) with metabolic syndrome components as intermediate markers and assess their associations with intima‐media thickness, left ventricular mass, and carotid‐femoral pulse‐wave velocity in an initially healthy population‐based family study. Methods and Results: This study included 1527 participants from the STANISLAS (Suivi Temporaire Annuel Non‐Invasif de la Santé des Lorrains Assurés Sociaux) cohort fourth examination. DPs were derived using reduced‐rank regression according to generation (G1: age ≥50 years; G2: age <50 years) and sex. Associations between DPs and cardiovascular damage were analyzed using multivariable linear regression models. Although identified DPs were correlated between generations and sex, qualitative differences were observed: whereas only unhealthy DPs were found for both men generations, healthy DPs were identified in G2 ("fruity desserts") and G1 ("fiber and w3 oil") women. The "alcohol, " "fast food and alcohol, " "fried, processed, and dairy products, " and "meat, starch, sodas, and fat" DPs in G1 and G2 men and in G1 and G2 women, respectively, were associated with high left ventricular mass (β [95% CI], 0.23 [0.10–0.36], 0.76 [0.00–1.52], 1.71 [0.16–3.26], and 1.80 [0.45–3.14]). The "alcohol" DP in G1 men was positively associated with carotid‐femoral pulse‐wave velocity (0.22 [0.09–0.34]). Conclusions: The DPs that explain the maximum variation in metabolic syndrome components had different associations with subclinical cardiovascular damage across generation and sex. Our results indicate that dietary recommendations should be tailored according to age and sex. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01391442.